Childfree Perspektif Hukum Islam dan Undang-Undang Hak Asasi Manusia di Indonesia - Safira, Nadia; Alfarisi, Usman; Mutiara, Diah; Nurhadi, Nurhadi; Fatmakartika, Rini (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The phenomenon of childfree, or the conscious decision of couples not to have children, has become a significant discourse in Indonesia. This paper aims to analyze childfree choices from the perspective of Islamic law and the Indonesian Human Rights Act. The research method used is normative juridical with a statutory and literature approach. The findings show that in Islamic law, the decision to be childfree is often considered contradictory to the purpose of marriage, one of which is procreation. However, from the human rights perspective, childfree is part of reproductive rights and individual freedom to determine their life. This analysis emphasizes the dialectic between religious norms and human rights, highlighting the need for dialogue to find common ground.